Estrategias de optimización bi-objetivo para el proceso de pesaje multicabezal (2019)
Multihead weighing processes are considered an important strategy in packaging companies. Multihead weighers are used for dosing a wide range of products, from granules to large products. The packaging process consists of choosing a subset of hoppers in the multihead weigher to form a product package. This paper proposes a set of filling strategies of hoppers to reduce the variability in the weight of the produced packages. The strategies are evaluated through a bi-objective optimization approach which aims to minimize the absolute difference between the target weight and the actual weight of the packages, while trying to maximize the selection of those hoppers with more time in the packaging system. In the bi-objective approach, the considered objectives are dynamically adjusted and managed in each packaging operation. In addition, the mathematical model and the packing algorithm are developed and presented. The results of the process performance parameters are obtained and analyzed to show the effectiveness of the proposed strategies. Also, conditions of minimum variability are identified and those can be used by the packaging industry where multihead weighers are used.